Phylogeny of urate oxidase producing bacteria: on the basis of gene sequences of 16S rRNA and uricase protein: Phylogeny of urate oxidase producing bacteria - Fatemeh Dabbagh,; Zahra Moradpour,; Abdollah Ghasemian,; Younes Ghasemi, (Iranian Journal of Pharmaceutical Sciences, 2012)
Uricase or Urate oxidase (urate:oxygen oxidoreductase, EC 1.7.3.3), a peroxisomal enzyme which is found in many bacteria, catalyzes the oxidative opening of the purine ring of urate to yield allantoin, carbon dioxide, and hydrogen peroxide. In this study, the phylogeny of urate oxidase (uricase) producing bacteria was studied based on gene sequences of 16S rRNA and uricase protein. Representative and type strains (52 strains total) of most of the known species were analyzed. The acquired sequences (rDNA sequences of the 16S rRNA genes and the amino acid sequences of uricase) were aligned with the Clustal W program using MEGA software version 4.0. Phylogenetic trees were constructed with the neighbor-joining method, and were bootstrapped with 500 replications of each sequence. The large congruence of phylogenetic relationship between the uricase gene and of 16S rRNA gives considerable support to the phylogeny of urate oxidase producing bacteria which was previously suggested on the basis of 16S rRNA sequences. The observed consistency promotes the idea that each of these genes shared a common evolutionary history in uricase producing bacteria we have analyzed.